PERANCANGAN USER EXPERIENCE SISTEM INFORMASI AKADEMIK UNTUK MENGURANGI PAIN POINTS DAN MENINGKATKAN USER SATISFACTION - Rahmani. AR, Muhammad Bayu; Pono, Nur Fajar; Ariandi, Muhammad (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2025)
Many Academic Information Systems (SIAKAD), including at Universitas Cahaya Bangsa, prioritize technical function over User Experience (UX), leading to significant pain points and low User Satisfaction. Key issues include the inefficient Course Registration System (KRS) flow (lack of automatic package enrollment) and minimal system feedback. This research aims to analyze and design a SIAKAD UX prototype to reduce daily administrative pain points and improve User Satisfaction using a Mixed Methods approach framed by User-Centered Design (UCD). The qualitative phase utilized in-depth interviews with five active users and subsequent user persona analysis to identify system pain points. The solution was implemented in a high-fidelity prototype (Figma), featuring the Automatic KRS Package Enrollment and a Real-time Notification Page. Quantitative evaluation using the System Usability Scale (SUS) involving 10 student respondents yielded a score of 88.0, categorized as Excellent. This strongly validates that the design, which focuses on flow efficiency and transparent feedback, successfully addresses the initial pain points. The study concludes that UCD is an effective strategic framework for boosting administrative efficiency and User Satisfaction within educational information systems